PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA PT BANK PANIN DUBAI SYARIAH TBK - Yenti, Elfina; Sari, Fera Yunita (Jurnal Akuntansi Syariah (JAkSya), 2023)
This study aims to see the effect of the disclosure of Corporate Social Responsibility (CSR) on firm value at PT Bank Panin Dubai Syariah Tbk. The type of research carried out in this study is causal association research that uses secondary data from financial statements and company annual reports with quantitative methods. The data collection technique used in this study is the documentation method. The data analysis technique used in this study is non-parametric statistics. From the research conducted, it can be concluded that with the Binomial test it can be seen that the value of the test proportion (test prop.) = 0.50. The proportion of observations for CSR = 0.50 and for Tobin's Q = 0.50. The result of the probability value of 2-way binomial extract (Exact Sig. (2-tailet) or p - value is 1,000, greater than 0.05, the conclusion that can be drawn is that H0 is accepted and Ha is rejected. This means that Corporate Social Responsibility (CSR) has no significant effect on Company Value at PT Bank Panin Dubai Syariah Tbk.